Ministry of Trade and Industry Decree No. 145 For The Year 2017 Amending the Export Duty Imposed on Certain Mineral Ores = وزارة التجارة والصناعة قرار رقم 145 لسنة 2017 فى شأن تعديل رسم الصادر على بعض الخامات التعدينية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic